Tingkat Kedisiplinan Ibadah Peserta Didik di SMPIT Dar El Iman Kota Padang - Miftahurrahmah, Miftahurrahmah; Wirdati, Wirdati (Lembaga Yasin AlSys, 2024)
This research aims to determine the level of religious discipline of students at SMPIT Dar El Iman, Padang City. This research uses a quantitative approach with a correlational type of research. The population in this study were students in grades 8 and 9 at SMPIT Dar el Iman. The sampling technique used simple random sampling, using the Slovin formula and 81 respondents were obtained. The data collection technique is by distributing questionnaires with a Likert scale, then the results are analyzed using Microsoft Excel. The results of the research show that the level of prayer discipline of students at SMPIT Dar El Iman, Padang City in the 5 daily obligatory prayers is 82.41% in the very good category, the sunnah careib mu'akkad prayer is 68.11% in the good category, the dhuha sunnah prayer is 71.30% in the good category. good, the tahajud sunnah prayer was 63.07 in the good category, the witir sunnah prayer was 62.35% in the good category, reading the morning and evening zikr was 86.42% in the very good category and reading the Koran was 88.58% in the very good category. Overall, The worship disscipline of students at SMPIT Dar el Iman is categorized as good with an overall average of 73.37%. The results of this research can be used as initial data for future researchers by examining different issues related to the problem and sharing issues relevant to this context.